A Brief Review of the Global and Indonesian Diagnostic Development for Sexual Transmitted Diseases - Giri-Rachman, Ernawati Arifin; Laurelia, Jessica; Marselina Irasonia, Tan; Wardono , Niloperbowo; Anindyajati (Current Research on Biosciences and Biotechnology, 2024)
Sexually transmitted diseases (STDs) are diseases with a high prevalence rate. The World Health Organization (WHO) estimates that more than 1 million STDs are transmitted every day, those diseases are chlamydia, syphillis, trichomoniasis, ghonorroea, and virus caused diseases (hepatitis B virus, immunodeficiency virus, human papillomavirus, and herpes simplex virus). Early and accurate examination and detection are important to help with the healing and control of these diseases. One of the examination methods that could be used is using the laboratory diagnostic methods which contribute to 40% to 60% of the process of diagnosing a disease. Thus, early detection not only helps control the spread of STDs but also facilitates the healing process. However, in Indonesia there are obstacles in the examination of diseases due to several factors, such as inadequate surveillance system and limited examination facilities, so that most people are undiagnosed. Therefore, this review will discuss in more depth the development of diagnostics for sexually transmitted diseases in Indonesia and globally. Global development in diagnostics is very broad and diverse, in which many diagnostic techniques has already been established. The development of diagnostic techniques has progressed rapidly from simplex assays to multiplex and also computerized assays. Diagnostic techniques in Indonesia has also developed and some of the local kits have already been in the market showing that Indonesia is already moving towards production of local diagnostics.